Effects of cyclic tensile strain and microgravity on the distribution of actin fiber and Fat1 cadherin in murine articular chondrocytes. (2nd December 2021) - Hatakeyama, Junpei; Nomura, Masato; Wakimoto, Yoshio; Inoue, Shota; Li, Changxin; Takamura, Daisuke; Akisue, Toshihiro; Moriyama, Hideki
Abstract: Chondrocytes as mechano-sensitive cells can sense and respond to mechanical stress throughout life. In chondrocytes, changes of structure and morphology in the cytoskeleton have been potentially involved in various mechano-transductions such as stretch-activated ion channels, integrins, and intracellular organelles. However, the mechanism of cytoskeleton rearrangement in response to mechanical loading and unloading remains unclear. In this study, we exposed chondrocytes to a physiological range of cyclic tensile strain as mechanical loading or to simulated microgravity by 3D-clinostat that produces an unloading environment. Based on microarray profiling, we focused on Fat1 that implicated in the formation and rearrangement of actin fibers. Next, we examined the relationship between the distribution of Fat1 proteins and actin fibers after cyclic tensile strain and microgravity. As a result, Fat1 proteins did not colocalize with actin stress fibers after cyclic tensile strain, but accumulated near the cell membrane and colocalized with cortical actin fibers after microgravity. Our findings indicate that Fat1 may mediate the rearrangement of cortical actin fibers induced by mechanical unloading.